Renewable Energy Sources: Global and Russian Outlook Up to 2040 - Galkina, Anna; Kulagin, Vyacheslav; Mironova, Irina (Journal of Technology Innovations in Renewable Energy, 2014)
During the period up to 2040, renewable energy sources (RES) will have the highest growth rates of all forms of energy. Based on the calculations on the world energy model incorporated in the SCANER modelling and information complex (working on the basis of optimization, econometric analysis, and balance approach), key trends in the world consumption of renewable energy sources; the share of OECD and non-OECD countries in the use of the renewable energy sources; consumption of renewable energy sources by type; end use and the impact on the electricity sector during the period up to 2040 were observed. The main finding of the paper is that RES are becoming more competitive and therefore will be used on an increasingly wide scale not only in the OECD countries, but also in the whole world. At the same time, due to the fact that RES start their take-off from a modest basis, they will only have a limited influence on the shares of hydrocarbons in the energy mix.